Technology Venture Blueprint Project Title : Peaceza Cafe / Nurzafirah Aidah Mohammed Zabani - Mohammed Zabani, Nurzafirah Aidah (2020)
Peaceza Café is a partnership that operates a food product service business in a restaurant or café. The business is located at No. 10, Jalan BPS 2, Bandar Prima, Senawang, 70450, Seremban, Negeri Sembilan, Malaysia. It is near to Mydin Senawang Supermarket. Peaceza Café produces the main meal that will become our signature food called Peaceza Pizza. Peaceza Pizza is a homemade double decker pizza. The Peaceza Pizza is made with our own recipe that would be a special and famous food. In addition, our business also provides various types of pizza’s topping that give high consumer satisfaction